Cyberbullying: Where Are We Now? A Cross-National Understanding - Conor Mc Guckin (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2017)
Cyberbullying has emerged as a major issue across societies and for schools, parents, children, and national governments (see Smith and Steffgen, 2013). Despite some similarities with traditional, or face-to-face (f2f) bullying (Mc Guckin, Cummins and Lewis, 2010), there is sufficient difference to warrant this contemporary and detailed examination of the issues related to cyberbullying-from a perspective that draws upon the most pertinent research and informed opinion from key researchers and thinkers from across the globe. The initial and pioneering knowledge about cyberbullying has now moved to a newer, more mature position that has been able to delineate the nuances associated with the issue, and importantly, yield robust insights for those involved in, or tasked to deal with, cyberbullying. This Special Issue brings together a collection of papers that represents the most up-to-date perspectives and evidence from across the globe. Collectively, these papers demonstrate how scholars and policy makers, from disparate disciplinary or stakeholder starting points, are progressing in their understanding of each other's language and requirements-thus facilitating the important move towards a more coherent and understandable agenda that seeks to minimize the potential risks to children and young people, understand the relationships between involvement in cyberbullying and associated biopsychosocial factors, in order to implement integrated and evidence-informed intervention and prevention programmes.